PHASE FORMATION PROCESSES IN STEEL – BENTONITE INTERFACE IN THE CONDITIONS OF RADIOACTIVE WASTE GEOLOGICAL REPOSITORY EVOLUTION - Shabalin B.; Lavrynenko O.; Buhera S.; Mitsiuk N. (Геохімія техногенезу, 2019)
The review work presents the analysis of up to date publications, including original ones, devoted to studying of nano-sized mineral phase formation processes on the interface surface of a bentonite buffer, mineral composition of which contains montmorillonite (70-90 mass%), and a steel container in the conditions of radioactive waste geological repository. Probable changes of mineralogical, geomechanical and hydraulic properties of bentonite during evolution of geological disposal have been considered. It is expected that ferric saponite, berthierine or chlorite may be formed as a result of phase transformations of the buffer material. It has been demonstrated that saponitization of the buffer will not significantly decrease its isolation properties due to ability of saponite to swell and similarity of its physicochemical properties to montmorillonite, while montmorillonite illitization may cause buffer insulating properties loss. Characterization of the germinal structures of Green Rust and Fe- ferrihydrite which can be formed on the surface of a steel container under geological disposal conditions, and contribute to radionuclides fixation on the steel-bentonite interface is presented. It is emphasized that it is necessary to carry out complex experimental researches, which will allow prediction of bentonite buffer long-term stability in geological repository conditions, taking into account mineralogical-geochemical processes caused by corrosion of steel containers. A change of physicochemical conditions, mineralogical, geomechanical and hydraulic properties of the bentonite during geological disposal facilities operation and closure which can lead to decrease of buffer insulating properties is considered. Particular attention need to be paid for the analysis of the processes, taking place on the bentonite buffer steel container interface. It has been shown that formation on the surface of old germinal structures of Green Rust and ferrihydride and their phase transformations into sorption-active phases of ferrum oxyhydroxides and oxides can become an additional mechanism for fixation of mobile forms of radionuclides and transfer them to a less mobile and toxic state by means of reduction. During contact of the ground-water saturated bentonite buffer with the steel surface, mineralogical changes of the bentonite are directed to processes of saponitization and beidelitization. While saponitization is not critical to buffer isolating properties because of the ability of saponite to swell, partial or complete formation of beidelite substantially worsens them. One of the main processes that can become critical for the bentonite isolation properties is illitization of montmorillonite, the rate of which depends on temperature, chemical composition of the aqueous medium (pH and alkaline cation concentration, especially K+), degree of bentonite saturation with water, and the ratio between dispersion phase and dispersion medium. While a predictive estimate shows impossibility of buffer illitization due to low temperature, the use of external building materials, in particular, cements may shift the balance and lead to transformation of the bentonite to illite. The article emphasizes the necessity of carrying out complex experimental researches that will allow to predict the long-term stability of the bentonite buffer in the conditions of geological repository existence, taking into account mineralogical-geochemical processes caused by corrosion of steel containers.